2011
DOI: 10.1080/07448481.2010.511364
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol-Related Emergency Department Visits Associated With Collegiate Football Games

Abstract: Community measures did not reduce alcohol-related visits to the ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Department of Health and Human Services, 2012). Tailgating (TG) and pregaming (PG) are prevalent in college and associated with increased levels of alcohol use and associated harms (e.g., Borsari et al, 2007a; Shook & Hiestand, 2011; Zamboanga, Schwartz, Ham, Borsari, & Van Tyne, 2010). There are both similarities and differences between TG and PG (e.g., drinking before another event with different contexts), making the two culturally accepted activities difficult to differentiate.…”
mentioning
confidence: 99%
“…Department of Health and Human Services, 2012). Tailgating (TG) and pregaming (PG) are prevalent in college and associated with increased levels of alcohol use and associated harms (e.g., Borsari et al, 2007a; Shook & Hiestand, 2011; Zamboanga, Schwartz, Ham, Borsari, & Van Tyne, 2010). There are both similarities and differences between TG and PG (e.g., drinking before another event with different contexts), making the two culturally accepted activities difficult to differentiate.…”
mentioning
confidence: 99%
“…This is consistent with prior data showing that men between the ages of 21–29 years are most likely to be intoxicated at college football games. 8 , 10 While the demographics of all those attending sporting events should be included for public awareness campaigns on responsible alcohol consumption, special care should be taken by universities in conjunction with public health experts to target this particular demographic. Given the recent increase in alcohol-related ED visits among college students in general, it is important that steps are taken to reduce the morbidity associated with high-risk alcohol consumption at mass-gathering events; and young males contribute significantly to that morbidity.…”
Section: Discussionmentioning
confidence: 99%
“… 7 A study conducted at Ohio State University found that stricter community and university alcohol policies were associated with increased alcohol-related ED visits. 8 Studies at the University of Iowa a few years later, however, showed that stricter alcohol policies were associated with decreased incidence of blood ethanol levels in severe intoxication range, as well as a non-significant decrease in the number of alcohol-related ED visits. 9 , 10 Researchers at a large Midwestern university found a linear increase in alcohol-related incidents in the three years after the implementation of stadium alcohol sales.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, if tests of such assumptions are verified-or disproved-by data, decisions related to staffing and hours of operation around such external events may be made with more confidence. Studies of the effects of external circumstances and large-scale events and circumstances (Friday the 13 th , hurricanes, sporting events) on use of emergency room services and outcomes serve as examples of how such tests can lead to better decisions about service delivery and staffing (Drobatz et al, 2009;Jena et al, 2017;Jerrard, 2009;Lo et al, 2012;McGreevy et al, 2010;Protty et al, 2016;Schuld et al, 2011;Shook & Hiestand, 2011;Smith & Graffeo, 2005).…”
Section: Introductionmentioning
confidence: 99%